Determinants for the cost of equity in agricultural cooperatives - Canassa, Bruno José; de Moura Costa, Davi Rogério (REBRAE, 2016)
Cooperatives have peculiarities regarding their equity. Among others, the equity is nontransferable and there is an obligation to refund if requested by the member. Also, the return on investment can be in the form of favorable prices, services and cash patronage. From these statements, the understanding of the motivation to increase capital in a cooperative becomes necessary. Therefore, the aim of this study was to estimate the cost of equity, parameter used by an investor to make a decision, and investigate its determinants. Using data from 2010 and 2011 for cooperatives in the states of São Paulo and Paraná, this study employed a technique adapted from Gordon’s model to find the return required by the member. It was also used a panel data technique to find estimators for the determinants mentioned by literature. The results pointed to the lack of significance of location in the composition of the cost of equity and the return on assets having predominant role, with little impact from the others. These results may be indicative of preference for present returns compared to future expectations, also the lack of investment options for the producer from Paraná. The progress of this work can develop a line of research beneficial to understanding the return expected by the member and the financing and administration of cooperatives, based on the refinement and adaptation of finance techniques to the reality of these organizations.